Seasonal improvements among women's collegiate soccer players using a one day per week aerobic interval training model - Favero, T.; Jackson, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In the United States, the women`s collegiate soccer season is 14 weeks long followed by 4 weeks of playoffs. Teams regularly compete twice per week leaving little time for technical and tactical training or physical training and recovery. One recent report showed a significant decline in VO2max among women soccer players despite 3 cardiovascular training sessions per week (Miller et al.). The aim of this study is to test the efficacy of a 1-day per week conditioning program that combines aerobic and interval training (Helgerud et al and Dupont e al). Methods: Sixteen female division I soccer athletes (age 19.43 years) agreed to participate in a study passed by the Universities Human Subjects committee. Athletes were evaluated just prior to and following the competitive season. Athletes were assessed for body weight, % fat mass and aerobic capacity using a incremental treadmill VO2max test. The one day per week training program was administered every Tuesday following a rest day on Monday. Competitions are typically Friday and Sunday. The training program consisted of repeat intervals at paces between 80-120% VO2max. Total time for interval work (# intervals x interval time) was not less than 16 minutes per session. Elevated Heart rate time was typically no less than 45 minutes which included active recovery. Results: There were no changes in body mass (60.30 +/- 5.93 vs. 60.52 +/- 5.59) or % body fat (15.46 +/- 2.64 vs 15.16 +/- 2.70) when comparing pre season to post season tests. Aerobic capacity increased significantly from 50.89 +/- 3.04 to 52.46 +/- 3.01 from preseason to post season (p < 0.05). Maximum heart rate and maximum ventilation (VE) remained unchanged during the season. Discussion: Conditioning for soccer remains varied and complex given the strength, speed, agility, aerobic and technical requirements of the game. Compared to most professional or club soccer leagues, the U.S. collegiate competitive season is short and the number of contests average 1.8 per week. Athletes are expected to have one day off per week and have an easy recovery day between games. Time for physical training is typically limited during the competitive season. We demonstrate that a one-day per week conditioning program based upon aerobic development as described by Helgerud et al and implemented using an interval model similar to that described by Dupont is sufficient to improve the aerobic capacity of a women`s collegiate team. Our result suggests that a thoughtfully designed one- day per week training program can improve team aerobic fitness during a short competitive season.